Joint immobilization prevents murine osteoarthritis and reveals the highly mechanosensitive nature of protease expression in vivo. - Burleigh, A; Chanalaris, A; Gardiner, MD; Driscoll, C; Boruc, O; Saklatvala, J; Vincent, T (2012)
OBJECTIVE: Mechanical joint loading is critical for the development of osteoarthritis (OA). Although once regarded as a disease of cartilage attrition, OA is now known to be controlled by the expression and activity of key proteases, such as ADAMTS-5, that drive matrix degradation. This study was undertaken to investigate the link between protease expression and mechanical joint loading in vivo. METHODS: We performed a microarray analysis of genes expressed in the whole joint following surgical induction of murine OA (by cutting the medial meniscotibial ligament). Gene expression changes were validated by reverse transcriptase-polymerase chain reaction in whole joints and microdissected tissues of the joint, including the articular cartilage, meniscus, and epiphysis. Following surgery, mouse joints were immobilized, either by prolonged anesthesia or by sciatic neurectomy. RESULTS: Many genes were regulated in the whole joint within 6 hours of surgical induction of OA in the mouse. These included Arg1, Ccl2, Il6, Tsg6, Mmp3, Il1b, Adamts5, Adamts4, and Adamts1. All of these were significantly regulated in the articular cartilage. When joints were immobilized by prolonged anesthesia, regulation of the vast majority of genes was abrogated. When joints were immobilized by sciatic neurectomy, regulation of selected genes was abrogated, and OA was prevented up to 12 weeks postsurgery. CONCLUSION: These findings indicate that gene expression in the mouse joint following the induction of OA is rapid and highly mechanosensitive. Regulated genes include the known pathogenic protease ADAMTS-5. Targeting the mechanosensing mechanisms of joint tissue may offer new strategies for disease modification.